Energy calibration of He-3, He-4 Neutron Proportional Counters - Manolopoulou, M.; Fragopoulou, M.; Stoulos, S.; Koukorava, C.; Zamani, M. (HNPS Advances in Nuclear Physics, 2020)
Two helium filled proportional counters (He-3, He-4) were irradiated with neu- trons in the energy range 0.025 eV - 10.7 MeV, in the Tandem accelerator, NCSR Demokritos, Athens. The full energy peak in He-3 proportional counter as well as the recoil peaks in He-3 and He-4 counters show linear dependence with neutron energy. A study of gamma ray contribution to the neutron spectra of He-4 counter was performed as a function of the pulse shaping time.